A mathematical model of guarding the frontier - Jačiauskas, Ignas (Lietuvos matematikos rinkinys, 1997)
This paper presents a mathematical model og guarding the frontier. Optimization problem is solved according to two criteria: 1) number of guards; 2) according to the length of the guards’ moving.